2016
DOI: 10.1186/s12891-016-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2 antagonist, PKRA7 suppresses arthritis in mice with collagen-induced arthritis

Abstract: BackgroundProkineticin 2 (PK2) expression is upregulated in mice with collagen-induced arthritis (CIA), an animal model of rheumatoid arthritis. The purpose of our study was to investigate the effects of PK2 inhibition on CIA.MethodsPK2, prokineticin receptor (PKR) 1, and PKR2 mRNA transcripts in the joints of CIA mice were measured by real-time PCR on Days 21, 28, and 35 (n = 15/day). Localization of PKR1 and PKR2 proteins was examined immunohistochemically. PKRA7, a PK2 antagonist, was administered intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…(18). PKR-A was also administered in an animal model of collagen-induced arthritis (31) and autoimmune encephalomyelitis (32). In our UPEC-infected model, IL-1β secretion and caspase-1 cleavage were decreased after PKR-A treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(18). PKR-A was also administered in an animal model of collagen-induced arthritis (31) and autoimmune encephalomyelitis (32). In our UPEC-infected model, IL-1β secretion and caspase-1 cleavage were decreased after PKR-A treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study gained ethical approval from Chinese Traditional Medicine (Wenzhou, China). Arthritis was induced and emulsified in complete Freund's adjuvant and injected intradermally into the tail with 200 µg of collagen II (14). Meanwhile, in treatment with gambogic acid group, mice were treatment with 2 mg/kg/3 day (intraperitoneal injection) for 28 days (15).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that PKRA7 is a PROK2 antagonist, which blocking the PROK2 expression, and consequently suppressing the tumorigenic and angiogenesis abilities of PROK2 and its downstream significantly pathways in glioma and pancreatic cells [ 10 ]. In another study, PKRA7 was administered intraperitoneally into collagen-induced arthritis (CIA) mice, and significantly inhibited the severity of arthritis [ 26 ]. Based on these evidences, PKRA7 as a candidate target reagent for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%